2001
DOI: 10.1093/humrep/16.5.831
|View full text |Cite
|
Sign up to set email alerts
|

Comet assay of cumulus cell DNA status and the relationship to oocyte fertilization via intracytoplasmic sperm injection*

Abstract: This paper postulates that in the ovary, the close association between the cumulus cells and the oocytes permits the fertilizing ability of the oocytes to be determined indirectly through cumulus cell DNA status. The objective was to use a modified comet assay to analyse cumulus cell DNA and relate the data to oocyte fertilization after intracytoplasmic sperm injection (ICSI) procedures. Oocytes were retrieved (n = 15 cases) and free-floating cumulus cells were pooled and smeared on clear glass slides to dry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 19 publications
4
44
1
1
Order By: Relevance
“…Similar results were reported by Nakahara et al A lower incidence of apoptosis in cumulus cells from fertilized oocytes compared with nonfertilized oocytes had been reported by several investigators (18,26,39). In contrast, Raman et al (29) showed that the fertilizing ability of oocytes (after ICSI) was positively correlated with the cumulus cell DNA status (Comet assay). In a recent report, Corn et al (31) did not find any correlation between apoptosis in cumulus cells and fertilization rate.…”
Section: Figuresupporting
confidence: 85%
See 2 more Smart Citations
“…Similar results were reported by Nakahara et al A lower incidence of apoptosis in cumulus cells from fertilized oocytes compared with nonfertilized oocytes had been reported by several investigators (18,26,39). In contrast, Raman et al (29) showed that the fertilizing ability of oocytes (after ICSI) was positively correlated with the cumulus cell DNA status (Comet assay). In a recent report, Corn et al (31) did not find any correlation between apoptosis in cumulus cells and fertilization rate.…”
Section: Figuresupporting
confidence: 85%
“…Moreover, our findings and previous work (29) suggest an indirect relationship between the fertilizing ability of the oocyte and the cumulus DNA status. Hakuno et al (41) also agreed that ''the increase in cumulus cell apoptosis may produce a fall away of cumulus cells from the oocyte, and would be the signal that the oocyte has attained competence for fertilization.''…”
Section: Figuresupporting
confidence: 81%
See 1 more Smart Citation
“…A relationship between the DNA fragmentation of the cumulus cells and nuclear maturity has been proposed (31). Others have proposed the content of inhibin A and B and activin A in the follicular fluid as biochemical markers for oocyte quality and fertilizing capacity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Comet assay uses single cell gel electrophoresis (SCGE) to analyze DNA fragmentation in individual cells, was first introduced in 1984 by Ostling and Johanson (16) who used neutral buffer conditions to study double-stranded DNA breaks (17). This assay is extensively used in somatic cells to measure genotoxic damage, especially single and double strands breaks and was originally applied to sperm by Singh (18).…”
Section: Comet Assaymentioning
confidence: 99%